STUDENT ACTIVITIES AND PERCEPTIONS OF WEB-BASED VIRTUAL LABORATORY: INSIGHT FROM PHYSICS LEARNING - Setiawan, Tulus; Suwanda, Rizki; Anshari, Said Fadlan; Ananda, Ria; Fanita, Fanita (Universitas Labuhanbatu, 2025)
Purpose-The implementation of web-based virtual laboratories in physics education has significant potential to enhance students' scientific process skills and conceptual understanding of physics. The objectives of this study are: (1) to analyze the impact of implementing an interactive web-based virtual laboratory in activitiy physics learning, and (2) to describe students' perceptions of the use of this virtual laboratory.Methodology-The research design follows a pre-experimental method with a one-shot case study approach. The population consisted of all twelfth-grade students, distributed across four classes with consisting of 24 students for the samples. Observations of students’ scientific process skills were conducted to assess the intervention's impact. A questionnaire was administered after the learning session to measure students’ SPS activities before and after the intervention.Findings—The results of the observational data analysis on scientific process skills revealed an average activity percentage of 90.3%, indicating that the interactive web-based virtual laboratory is highly effective in supporting virtual practical-based learning. Additionally, the analysis of students' perceptions showed an average perception score of 86.42%, categorized as